Optimizing Educational Infrastructure Maintenance Through School-Committee Partnership Management - Suwandari, Lilis; Suryana, Cecep (Papanda Publisher, 2025)
Educational infrastructure maintenance requires effective collaboration between schools and community stakeholders, yet limited research examines the management processes that optimize these partnerships. This study analyzed partnership management between schools and school committees in educational infrastructure maintenance to identify effective collaborative mechanisms and implementation challenges. A qualitative multiple case study was conducted at two public elementary schools in Cianjur Regency, West Java: SDN Puncak 2 Cipanas and SDN Muhara Pacet. Ten participants including principals, committee chairpersons, teachers, parents, and students were selected through purposive sampling. Data collection employed semi-structured interviews, participant observation, and document analysis. Thematic analysis was conducted using Terry's management framework focusing on planning, organizing, implementing, and monitoring functions. Significant variations emerged in partnership effectiveness between research sites. SDN Puncak 2 Cipanas demonstrated systematic management approaches across all functions, achieving high community participation, diversified funding sources, and structured accountability mechanisms. SDN Muhara Pacet exhibited developing partnership characteristics with limited community engagement, basic planning processes, and informal monitoring systems. Key success factors included committee experience, clear organizational structure, transparent communication, and established role definitions. Primary challenges encompassed budget constraints, inconsistent community participation, and inadequate technical expertise. The findings support Terry's management framework application in educational contexts and validate the importance of systematic partnership development. Results align with social capital theory, demonstrating that effective infrastructure maintenance requires sustained relationship building and community mobilization. Schools with mature committees showed superior outcomes through enhanced stakeholder engagement and diversified resource mobilization strategies, confirming the critical role of organizational development in partnership success.